Improving permeability and antifouling performance of poly (ether ether ketone) membranes by photo-induced graft polymerization. (June 2020) - Huang, Tingjian; Li, Junfeng; Chen, Yuan; Zhong, Tianhaoyue; Liu, Pengqing
Graphical abstract: Highlights: Poly (ether ether ketone) membranes were grafted by photo-induced polymerization. Permeability and antifouling performance depend strongly on the grafting degree. The chain length is more influencing than graft density on membrane permeability. The long graft chains are required for excellent antifouling performance. Abstract: Poly (ether ether ketone) (PEEK) ultrafiltration membrane was modified with 2-hydroxylethyl acrylate (HEA) as a hydrophilic monomer through light-initiated grafting polymerization to improve its permeability and antifouling property. The effects of monomer concentration and irradiation time on the surface's chemical structure and morphology, degree of grafting (DG), surface hydrophilicity and pore volume of the membranes were systematically investigated; meanwhile, the antifouling property were characterized and analyzed using bovine serum albumin (BSA) as a model foulant. The results indicate that the DG and hydrophilicity of the membrane surface are enhanced with the increase of either monomer concentration or irradiation time. The water flux of modified membrane using 0.3 mol/L HEA and 20 min irradiation time is 1.52 times that of unmodified membrane, and the irreversible fouling decreases from 51 % to 10.9 %. In this work, the graft chain length and graft density are considered to be controlled by the factors of monomer concentration and irradiation time, respectively. Compared with increasing the graft density, the increase of the graft chain length is more easily to lead to a decrease in membrane permeability. Meanwhile, the long chain length is more important than the high graft density to achieve excellent antifouling performance.